FIQH TEACHER STRATEGIES FOR STRENGTHENING WORSHIP AWARENESS IN JUNIOR MADRASAH STUDENTS: A FOUR-STAGE OPERATIONAL MODEL - Agustina, Juli; Adilla, Ulfa; Mabruri; Norullah; Dhinika, Rahma; Andryadi (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study examined how Fiqh teachers at Madrasah Tsanawiyah Darul Ma’arif, Tanah Periuk, Bungo Regency, Jambi Province, sustained students’ worship practice through the 2025 odd semester. A qualitative case study was conducted between July and October 2025 with three Fiqh teachers, the head of madrasah, and twenty-two Grade VIII–IX students. Data were collected through 23 classroom and prayer-room observations, semi-structured interviews and document analysis of attendance logs and lesson plans. Coding followed the Miles–Huberman–Saldaña procedure, and inter-rater agreement reached Cohen’s kappa of 0.81. Five strategies were identified, with proportional use of direct exemplarity at 31%, worship habituation at 26%, religious motivation at 19%, supervision and evaluation at 16%, and family–school communication at 8%. Attendance at five anchor practices rose between baseline and follow-up: dhuhr congregational prayer from 62% to 89%, Friday tadarus from 48% to 78%, asma’ul husna recitation from 71% to 93%, pre-class du’a from 84% to 97%, and Friday muhasabah from 55% to 82%. A four-stage workflow linked diagnostic assessment, strategy design, classroom enactment, and reflective evaluation in an iterative loop. The findings suggest that worship awareness develops most consistently when teacher exemplarity and structured habituation operate in tandem rather than in isolation, and that the workflow offers a transferable template for similar madrasah settings